Effect Of Performance Expectancy And Social Influence On Continuance Intention In OVO - Zoel Hutabarat; Ian Nurpatria Suryawan; Richard Andrew; Februarga Padua Akwila (Jurnal Manajemen, 2022)
The development of online transactions is driving the development of technology in payment systems. One of the most popular electronic money services in Indonesia is OVO. Behind OVO's rapid market share growth, system maintenance problems often arise that often occur without notice and are of long duration. This phenomenon is a doubt of consumers to continue to use OVO in the long term going forward because it does not match expectations and consequently consumers will look for alternative payments. This experience makes consumers unable to feel the price saving program offered and consequently consumers become dissatisfied. This study used a sample of 200 respondents, with a purposive sampling method, and with a questionnaire of 24 indicators. The result found that there is the influence of performance expectancy, social influence on continuance intention. Meanwhile, there is no relation to variable effort expectancy, price saving orientation and facilitating conditions to continuance intention.